Utilization of Banana Extract for Eco-friendly Functional Finishing of Textile Materials: A review - A. Ahmed, Mutasim; E. Abbas1, Amel (Gezira Journal of Engineering and Applied Sciences; Vol 13 No 2 (2018), 2019)
With the consumer's enhanced awareness of eco-safety, there has been an increasing tendency towards the use of sustainable and environmentally friendly materials. Thus considerable attention has been given to products from plants, for use in various industries notably in the textile industry. Among these plants banana is selected for this review, since it is the second largest produced fruit after citrus, contributing about 16% of the world’s total fruit production. This review provides literature information about classification of functional finishing, some important finishes, and their evaluation tests methods. In addition to focus on recent researches concerning utilization and application of banana extract for various textile finishing purposes such as coloration, deodorizing, flame retardant, UV protection, antimicrobial activity, and other important applications around the world for producing appealing and highly functional value-added textiles such as fibers, dyes , pigments, polyphenols, and other biologically active compounds.